2008
DOI: 10.1248/bpb.31.1917
|View full text |Cite
|
Sign up to set email alerts
|

Validation of 13C-Acetic Acid Breath Test by Measuring Effects of Loperamide, Morphine, Mosapride, and Itopride on Gastric Emptying in Mice

Abstract: The 13 C-breath test is used in clinical diagnosis of gastric emptying disorders. The gastric emptying rate can be assessed easily by breath tests using a 13 C isotope-labeled substance.1) The orally administered 13 C-labeled substance is not absorbed in the stomach, but rapidly absorbed in the duodenum and then metabolized in the liver to be released as 13 CO 2 . Therefore, the 13 C-breath test reflects gastric emptying rates and can monitor time-dependent changes in gastric motility in humans.Most rat or mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…This test is an accurate, noninvasive, simple method, without radiation exposure, and represents a reliable alternative to scintigraphy, the gold standard for measuring gastric emptying (4,34). Test solutions were labeled with 50 mg of [ 13 C]sodium acetate, which is rapidly absorbed in the duodenum, transported to the liver, and metabolized to 13 CO2 (22). Subjects were asked to exhale through a mouthpiece to collect an end-expiratory breath sample into a 100-ml foil bag.…”
Section: Assessment Of Gastric Emptyingmentioning
confidence: 99%
“…This test is an accurate, noninvasive, simple method, without radiation exposure, and represents a reliable alternative to scintigraphy, the gold standard for measuring gastric emptying (4,34). Test solutions were labeled with 50 mg of [ 13 C]sodium acetate, which is rapidly absorbed in the duodenum, transported to the liver, and metabolized to 13 CO2 (22). Subjects were asked to exhale through a mouthpiece to collect an end-expiratory breath sample into a 100-ml foil bag.…”
Section: Assessment Of Gastric Emptyingmentioning
confidence: 99%
“…On the other hand, 13 C-breath tests have been developed recently as a nonradioactive alternative in clinical study. The 13 C-labeled urea breath test, in particular, has been widely employed clinically to monitor Helicobacter pylori infections.…”
Section: Introductionmentioning
confidence: 99%
“…The 13 C-labeled urea breath test, in particular, has been widely employed clinically to monitor Helicobacter pylori infections. In addition, the [1-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In basic research, we have already reported a simple and non-invasive breath test system for evaluating gastric emptying and pancreatic exocrine secretion in conscious rats (Uchida et al, 2005;Uchida et al, 2007;Uchida et al, 2008;Matsumoto et al, 2008;Uchida et al, 2011). Moreover, we have also established a non-invasive and feasible method for the evaluation of rat gastrocecal transit time by using lactose-[ 13 C] ureide (Uchida et al, 2009a) and the effect of atropine sulfate which significantly delayed the gatsrocecal transit time (Uchida et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%